Answer:
f(x) = -3(x+3)(x-1)
Step-by-step explanation:
x = -3 & 1; f(x) = 9
f(x) = a(x-r1)(x-r2)
f(0) = a(x-r1)(x-r2) = 9; 9 = a(0-(-3))(0-1)
9 = a(3)(-1); 9 = a(-3)
a = -3
f(x) = -3(x+3)(x-1)
Answer: 16
Step-by-step explanation: 20/2 = 10
10x=160
10x/10=160/10
x=16
To get that, you have to multiply the both numbers, which is 24*12=288
![Y= x^2 -5](https://tex.z-dn.net/?f=Y%3D%20x%5E2%20-5)
We need to solve for x, we need to get x alone
![Y= x^2 -5](https://tex.z-dn.net/?f=Y%3D%20x%5E2%20-5)
Lets start by removing -5
Add 5 on both sides
![y + 5= x^2 -5 + 5](https://tex.z-dn.net/?f=y%20%2B%205%3D%20x%5E2%20-5%20%2B%205)
![y + 5= x^2](https://tex.z-dn.net/?f=y%20%2B%205%3D%20x%5E2)
Now to isolate x , we need to remove the square from x
To remove square , take square root on both sides
![+-\sqrt{y+5} = \sqrt{x^2}](https://tex.z-dn.net/?f=%2B-%5Csqrt%7By%2B5%7D%20%3D%20%5Csqrt%7Bx%5E2%7D)
square and square root will get cancelled
![+-\sqrt{y+5} = x](https://tex.z-dn.net/?f=%2B-%5Csqrt%7By%2B5%7D%20%3D%20x)
So
and ![x = -\sqrt{y+5}](https://tex.z-dn.net/?f=x%20%3D%20-%5Csqrt%7By%2B5%7D)
Answer:
You go to whoever's question you wanna answer and it should say "add answer" and just type out your answer and solve it